The Influence of Transformational Leadership on Employee Performance in Financial Agencies and Regional Opinions Mandailing Natal Regency - Abdul Hakim Nasution; Mesra B (International Journal of Management, Economic and Accounting, 2024)
This research was a quantitative associative causal study aimed at analyzing the relationship patterns between variables and determining the influence of independent variables (exogenous) on the dependent variable (endogenous). The research was conducted at the Office of the Regional Financial and Revenue Agency of Mandailing Natal Regency, with a population of 85 employees. The sampling technique used was saturated sampling, where all members of the population were selected as samples. The data were obtained through questionnaires distributed to all employees from various divisions. The results showed that Transformational Leadership had a positive and significant effect on Employee Performance. This was evidenced by the t-count value of 16.245, which was greater than the t-table value of 1.66298, and the significance value of 0.000, which was smaller than 0.05. The regression coefficient of 1.529 indicated that every 1-point increase in Transformational Leadership would lead to an increase of 1.529 points in Employee Performance, assuming other variables remained constant. Additionally, the coefficient of determination test showed an Adjusted R Square value of 0.873 or 87.3%, indicating that Transformational Leadership had a very high impact on Employee Performance, with 12.7% being influenced by other factors not examined in this study. Overall, the results of this study identified that improving Transformational Leadership could contribute to enhancing Employee Performance at the Office of the Regional Financial and Revenue Agency of Mandailing Natal Regency.